Distribution of starch, lipid and nuclei in xylem and phloem of Tectona grandis Linn. - Islam, Md Azharul; Begum, Shahanara (Journal of Bio-Science, 2012)
Context: Reserve materials among different plant tissues vary species to species. The distribution pattern of such materials and cell death pattern in Tectona grandis Linn. are still obscure. Objectives: To study the localization of starch, lipid and nuclei in the phloem, cambium and xylem tissue of T. grandis. Materials and Methods: Blocks containing phloem, cambium and outermost xylem of the stem of 12 years old teak tree collected. Different staining methods used to visualize starch, lipid and nuclei within different cells under light microscope. Results: Starch in parenchyma cells is more abundant in outer xylem than phloem and cambium. Lipids droplets are uniformly distributed in outermost xylem. Phloem parenchyma content few mass of lipids but, limited in cambium. There are many dead cells visualized in both phloem and xylem with characteristic patterns. The results clarify the levels of starch, lipid in tissue of T. grandis and showed distinguished variation among the cell contents. Conclusion: The physiology of plant cells related to transport of nutrients and cell death also illustrated in the report. This would be helpful for further study to improve quality wood through tree breeding program. DOI: http://dx.doi.org/10.3329/jbs.v19i0.12997 J. bio-sci. 19: 29-35, 2011